Managing people an activity CD for tutors and trainers - Thompson, Rosemary; Thomson, Andrew; Giles, Ken ([Oxford] : Elsevier, 2005)
This CD-ROM is packed full of tutor resource material for those delivering management training. Includes activities, scenarios, case studies, role plays, information gethering and feedback for teaching participants in HR management
Keywords: Personnel management; Performance -- Management; Organizational effectiveness; Employee motivation